2021
DOI: 10.24018/ejdent.2021.2.3.63
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Maternal, Perinatal, and Early Infancy Period on the Eruption Timing of the First Primary Tooth

Abstract: Aim: The aim of this study is to identify and review the literature on effect of perinatal and early infancy factors on the eruption chronology of the first deciduous tooth. Materials and methods: A PubMed database literature survey regarding the influence of maternal, perinatal and early infancy period factors on eruption timing of the first primary tooth covering the period from January 1964 to 2020 was conducted. Results: Maternal factors such as smoke exposure during pregnancy, gestational age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…It is thought that birth weight may indirectly affect tooth eruption age by affecting tooth development [ 27 ]. Our analysis results showed a negative relationship between birth weight and ETFPT, similar to previous studies [ 1 , 2 , 4 , 17 , 30 ]. Contrary to these studies, Alnemer et al [ 3 ] found no relationship between the birth weight of the infant and the ETFPT.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It is thought that birth weight may indirectly affect tooth eruption age by affecting tooth development [ 27 ]. Our analysis results showed a negative relationship between birth weight and ETFPT, similar to previous studies [ 1 , 2 , 4 , 17 , 30 ]. Contrary to these studies, Alnemer et al [ 3 ] found no relationship between the birth weight of the infant and the ETFPT.…”
Section: Discussionsupporting
confidence: 92%
“…There is a positive correlation between late eruption and low birth weight due to the general developmental delay in these children [ 9 ]. This supports the assumption that malnourished children in the prenatal period, when teeth are just beginning to form, suffer from nutritional problems that can negatively impact the development of their primary teeth [ 1 , 9 ]. In terms of chronological age, the eruption time of primary teeth was delayed in preterm children, and this was found to be related to non-breastfeeding and very low birth weight [ 13 ].…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Logan´s human dental eruption chronology table, modified by McCall and Schour [ 7 ], is still accepted worldwide as a standard for a long time, although its findings were obtained, a long time ago, from the dissection of a few children´s cadavers from a specific population (European) and through a methodology that has not been well described. Other researchers have pointed out that the eruption occurred at least two months later in low-income countries [ 8 15 ], indicating that the origin, ethnicity, among other individual characteristics, can influence the chronology [ 2 , 3 , 13 21 ]. So, these variations should be considered in the development of a new standard for tooth eruption patterns, that cannot be universally applied owing to ethnic variations.…”
Section: Introductionmentioning
confidence: 99%